1983
DOI: 10.1128/aac.23.5.790
|View full text |Cite
|
Sign up to set email alerts
|

Cefonicid concentrations in serum and atrial tissue during open-heart surgery

Abstract: Cofiicid was administered iutafnuscularly 1 h before open-heart surgery to seyenk2tlents in doses Af 1 gaich and to s1x'pdtients in doses of 2 ' ea;h. Cef*ia cooiicentrations wpre m ured in the right atrial biopsy ap in serum at onset ofsurSry, at time otatriE-biopsy, 15 mim after starting cardiopulmonary bypass, and at completion of cardiopulmonary bypass. Concentrations in the atrial biopsy and in serum at all periods exceeded the minimal inhibitory concentrations for organisms most frequently responsible fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1984
1984
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
1
1
Order By: Relevance
“…Cefonicid concentrations in the atrial appendage and penetration ratios were markedly higher in our study than those recently reported by Sterling et al after a comparable 2-g dose (15). However, there are a few differences in study design that account for these differences.…”
Section: Resultscontrasting
confidence: 56%
“…Cefonicid concentrations in the atrial appendage and penetration ratios were markedly higher in our study than those recently reported by Sterling et al after a comparable 2-g dose (15). However, there are a few differences in study design that account for these differences.…”
Section: Resultscontrasting
confidence: 56%
“…[28][29][30][31][32] Cefonicid depends on renal mechanisms for its elimination, with -90 percent of the drug excreted unchanged over 24 hours. Cefonicid's half-life increases to 50 hours in patients with severe renal impairment.…”
Section: Pharmacokineticsmentioning
confidence: 99%